Efficacy of Metarhizium anisopliae (Metsch.) Sor. against the oriental migratory locust, Locusta migratoria manilensis Meyen - Santiago, D. S.; Castillo, A. G.; Arapan, R. S.; Navasero, M. V.; Eusebio, J.E. (2001)
Isolates of the pathogenic fungus, Metarhizium anisopliae (Metsch.) Sor., were screened for virulence against nymphs of the Oriental migratory locust, Locusta migratoria manilensis Meyen, in a feeding assay using corn leaves contaminated with aqueous spore suspension at a density of 107 conidia mL-1. The most virulent was isolate Fm11 with a median lethal time (LT50) of 5.1 days. When assayed at a density of 108 conidia mL-1, the LT50 of Fm11 was reduced to 3.1 days. This isolate was also infectious to nymphs topically inoculated with 15,000 conidia per individual on the abdomen and mouthparts. Coconut-oil-based formulation of isolate Fm11 applied as ultralow volume spray or aqueous suspension applied as high volume spray at 3.0 × 1012 conidia ha-1, resulted in up to 98% mortality of nymphs in field tests. Most mortalities occurred between 4 and 9 days. Mortality peaks occurred at day 4 post-application for the oil-based formulation and at day 6 or 7 for the aqueous spore suspension.
Keywords: Locusts; Locusts -- Control; Control of agricultural pests and diseases; Fungi as biological pest control agents; Fungal pathogen